-
Notifications
You must be signed in to change notification settings - Fork 38
Commit
This commit does not belong to any branch on this repository, and may belong to a fork outside of the repository.
- Loading branch information
Showing
1 changed file
with
38 additions
and
1 deletion.
There are no files selected for viewing
This file contains bidirectional Unicode text that may be interpreted or compiled differently than what appears below. To review, open the file in an editor that reveals hidden Unicode characters.
Learn more about bidirectional Unicode characters
Original file line number | Diff line number | Diff line change |
---|---|---|
@@ -1 +1,38 @@ | ||
\workinprogress % TODO | ||
Let $X$ denote the number of tosses until some bin contains two balls. | ||
Assume that after $k$ tosses, where $1\le k\le b$, no bin contained more than one ball, and let's calculate the chances that after the $(k+1)$st toss that condition holds. | ||
After the $k$ tosses, exactly $k$ bins are occupied and the $(k+1)$st ball falls in an empty bin with a probability | ||
\begin{align*} | ||
p_{k+1} &= \Pr{X>k+1\mid X>k} \\ | ||
&= \frac{b-k}{b}. | ||
\end{align*} | ||
More than $k$ tosses is required, when none of the first $k-1$ balls ended up in an occupied bin, so | ||
\begin{align*} | ||
\Pr{X>k} &= \prod_{i=1}^kp_i \\ | ||
&= \frac{b}{b}\cdot\frac{b-1}{b}\cdot\frac{b-2}{b}\cdots\frac{b-k+1}{b} \\[1mm] | ||
&= \frac{(b-1)(b-2)\cdots(b-k+1)}{b^{k-1}}. | ||
\end{align*} | ||
For $k=1$, 2, \dots, $b$, we have | ||
\begin{align*} | ||
\Pr{X=k+1} &= \Pr{X>k}-\Pr{X>k+1} \\ | ||
&= \frac{(b-1)(b-2)\cdots(b-k+1)}{b^{k-1}}-\frac{(b-1)(b-2)\cdots(b-k)}{b^k} \\[1mm] | ||
&= \frac{b(b-1)\cdots(b-k+1)-(b-1)\cdots(b-k+1)(b-k)}{b^k} \\[1mm] | ||
&= \frac{(b-1)\cdots(b-k+1)(b-(b-k))}{b^k} \\ | ||
&= \frac{b!\,k}{(b-k)!\,b^{k+1}}. | ||
\end{align*} | ||
Then, the expected value of $X$ is | ||
\begin{align*} | ||
\E{X} &= \sum_{k=0}^b(k+1)\Pr{X=k+1} \\ | ||
&= \frac{b!}{b^b}\sum_{k=0}^b\frac{b^{b-k}k}{(b-k)!\,b}\,(k+1) \\ | ||
&= \frac{b!}{b^b}\sum_{k=0}^b\frac{b^k(b-k)}{k!\,b}\,(b-k+1) \\ | ||
&= \frac{b!}{b^b}\left(\sum_{k=0}^b\frac{b^kb}{k!\,b}\,(b-k+1)-\sum_{k=0}^b\frac{b^kk}{k!\,b}\,(b-k+1)\right) \\ | ||
&= \frac{b!}{b^b}\left(\sum_{k=0}^b\frac{b^k}{k!}\,(b-k+1)-\sum_{k=1}^b\frac{b^{k-1}}{(k-1)!}\,(b-k+1)\right) \\ | ||
&= \frac{b!}{b^b}\left(\sum_{k=0}^b\frac{b^k}{k!}\,(b-k+1)-\sum_{k=0}^{b-1}\frac{b^k}{k!}\,(b-k)\right) \\ | ||
&= \frac{b!}{b^b}\left(\sum_{k=0}^b\frac{b^k}{k!}\,(b-k+1)-\sum_{k=0}^b\frac{b^k}{k!}\,(b-k)\right) \\ | ||
&= \frac{b!}{b^b}\sum_{k=0}^b\frac{b^k}{k!}. | ||
\end{align*} | ||
Note that the summation in the last step is a partial sum of the Maclaurin series of $e^b$ (see page 65 of the book), and as $b$ grows, that approximation is more accurate. | ||
We can therefore bound the summation by $\Theta(e^b)$, and after applying Stirling's approximation (3.25) to $b!$ we get | ||
\begin{align*} | ||
\E{X} &= \Theta\left(\frac{\sqrt{2\pi b}\,\bigl(b^b\!/e^b\bigr)}{b^b}\right)\cdot\Theta(e^b) \\ | ||
&= \Theta\bigl(\sqrt{b}\bigr) && \text{(by \refProblem{3-5}(d))}. | ||
\end{align*} |